Effect of Central Sympathoinhibition With Moxonidine on Sympathetic Nervous Activity in Polycystic Ovary Syndrome—A Randomized Controlled Trial - Shorakae, Soulmaz; Lambert, Elisabeth A.; Jona, Eveline; Ika Sari, Carolina; de Courten, Barbora; Dixon, John B.; Lambert, Gavin W.; Teede, Helena J. (Frontiers in Physiology, 2018)
Sympathetic nervous system (SNS) activity is increased in polycystic ovary syndrome (PCOS). Moxonidine is a centrally acting sympatholytic drug with known beneficial effects on hypertension, insulin sensitivity, dyslipidemia and inflammation. In this double-blind placebo controlled randomised clinical trial we examined the effect of moxonidine on modulating sympathetic activity and downstream metabolic abnormalities in 48 pre-menopausal women with PCOS (Rotterdam diagnostic criteria), recruited from the community (January 2013 - August 2015). Participants received moxonidine (0.2mg daily initially, up titrated to 0.4mg daily in 2 weeks) (n=23) or placebo (n=25) for 12 weeks. Multiunit muscle sympathetic activity (by microneurography) and plasma noradrenaline levels were measured (primary outcomes). Fasting lipids, insulin resistance, serum androgens and inflammatory markers were measure as secondary outcomes. Forty three women completed the trial (19 moxonidine, 24 placebo). Mean change in burst frequency (-3±7 vs -3±8 per minute) and burst incidence (-3±10 vs -4±12 per 100 heartbeat) did not differ significantly between moxonidine and placebo groups. Women on moxonidine had a significant reduction in hs-CRP compared to placebo group (-0.92±2.3 vs -0.04±1.5) which did not persist post Bonferroni correction. There was a significant association between markers of insulin resistance at baseline and reduction in sympathetic activity with moxonidine. Moxonidine was not effective in modulating sympathetic activity in PCOS. Anti-inflammatory effects of moxonidine and a relationship between insulin resistance and sympathetic response to moxonidine are suggested which need to be further explored. Clinical Trial registration number: (NCT01504321)